1982
DOI: 10.1161/01.res.50.1.140
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the adrenal and renal responses to angiotensin II fetal lambs and adult sheep.

Abstract: SUMMARY The adrenal and renal responses to similar increases in plasma angiotensin II (All) were studied in chronically catheterized fetal lambs (112-131 days gestation; term 145 days) and adult nonpregnant sheep. The rate of All infusion was adjusted to compare the effect of similar rises in plasma AH concentration between fetuses and adult ewes. Increases in plasma All were associated with a decrease in plasma renin activity (PRA) in both fetuses (5.55 ± 1.53 to 2.11 ± 0.59 ng/ml per hr, P < 0.05) and adult … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
35
0

Year Published

1984
1984
2012
2012

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(39 citation statements)
references
References 45 publications
(49 reference statements)
4
35
0
Order By: Relevance
“…For example, AT1 receptor gene expression in the kidney of sheep remains relatively constant throughout the latter part of gestation and early newborn period and decreases •10 days after birth (Robillard et al 1994), although the physiological consequences of this on renal vascular tone are not known. In mid-term fetal sheep, however, angiotensin II administration is associated with a reduction in renal blood flow measured using radiolabelled microspheres (Robillard et al 1982b), this effect being similar in fetal and adult sheep. Moreover, in our laboratory, we have shown in conscious lambs that administration of the angiotensin converting enzyme inhibitor, captopril, is associated with a marked decrease in renal blood flow .…”
Section: Discussionmentioning
confidence: 87%
“…For example, AT1 receptor gene expression in the kidney of sheep remains relatively constant throughout the latter part of gestation and early newborn period and decreases •10 days after birth (Robillard et al 1994), although the physiological consequences of this on renal vascular tone are not known. In mid-term fetal sheep, however, angiotensin II administration is associated with a reduction in renal blood flow measured using radiolabelled microspheres (Robillard et al 1982b), this effect being similar in fetal and adult sheep. Moreover, in our laboratory, we have shown in conscious lambs that administration of the angiotensin converting enzyme inhibitor, captopril, is associated with a marked decrease in renal blood flow .…”
Section: Discussionmentioning
confidence: 87%
“…Hematocrit was determined in duplicate using a micrometer caliper. RIA, previously established in our laboratory, were used to measure plasma cortisol (22), plasma A11 (25) concentrations, and PRA (25,26).…”
Section: Methodsmentioning
confidence: 99%
“…(6). The technique, reliability, and full characterization of this assay in our laboratory have been reported recently (22).…”
Section: Methodsmentioning
confidence: 99%
“…Previous in vitro studies (3, 8, 20,32,33) have shown that the fetal adrenal gland has the ability to synthesize and secrete aldosterone following stimulation by either A-I1 (33), ACTH (33), or increasing potassium concentration (32). More recently, we (2 1, 22) and others (27) demonstrated that in vivo elevation of plasma A-I1 concentration stimulates aldosterone secretion during the last trimester of gestation in fetal lambs but to a lesser degree than in adult ewes (22). However, in vivo attempts to stimulate aldosterone secretion by ACTH (1,5 ) or potassium infusion (3 1) have been unsuccessful, suggesting a relative insensitivity of the fetal adrenal to these stimuli.…”
Section: Abbreviationsmentioning
confidence: 97%